2011
DOI: 10.4300/jgme-d-10-00233.1
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Institutional Resident Curriculum in Communication Skills

Abstract: Objective We describe a collaboration between the graduate medical education office and the Henry Ford Health System's Office of Clinical Quality and Safety to create an institution-wide communication skills curriculum pertinent to the institution's safety and patient- and family-centered care initiatives. Methods A multidisciplinary committee provided oversight for the curriculum design and used sentinel event and other qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…Data collected from the training included resident skill self-assessment, which significantly increased pre to post. 10 However, most of the reported trainings have included only a few participants; none of them evaluated improvements in informed consent communication and documentation skills. We hypothesized that a short intervention for residents highlighting critical aspects of informed consent would improve resident performance in both communication and documentation skills.…”
mentioning
confidence: 99%
“…Data collected from the training included resident skill self-assessment, which significantly increased pre to post. 10 However, most of the reported trainings have included only a few participants; none of them evaluated improvements in informed consent communication and documentation skills. We hypothesized that a short intervention for residents highlighting critical aspects of informed consent would improve resident performance in both communication and documentation skills.…”
mentioning
confidence: 99%
“…For example, 2.5 hr of training with faculty and standardized patients improved surgery residents ability to properly perform on an 8 item checklist from 6.85 to 7.40 items [5]. Direct feedback from standardized patients has also been found to be helpful to teach informed consent [6], as has an online module, a small group discussion with faculty, and standardized patient cases [7]. Training in medicine has relied on acquisition of knowledge and skills via an apprenticeship model utilizing real-world experience with actual patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated a correlation between effective health provider-patient communication and improved patient health outcomes [Glickman,2010;Jaipaul, 2011]. Patient centeredness has been increasingly advocated and incorporated into the training of healthcare providers [Philibert;2011;Joyce, 2011]. Increasing focus on patient-centered outcomes has led graduate medical education programs to incorporate patientcentered communication training programs in curricula.…”
Section: Introductionmentioning
confidence: 99%